Clinical and diagnostic difficulties in management of patients with laminopathies - O. V. Melnik; A. B. Malashicheva; Yu. V. Fomicheva; A. A. Khudyakov; A. Ya. Gudkova; D. I. Rudenko; M. A. Simonenko; Е. N. Mikhailov; D. S. Lebedev; E. S. Vasichkina; T. M. Pervunina; A. A. Kostareva (Российский кардиологический журнал, 2019)
Mutations in the LMNA gene cause developing of several phenotypes, both with isolated involvement of cardiac, muscle, adipose and bone tissues, and with their combination. The dominance of cardiovascular signs in the clinical performance and false clarity in nosology definition can cause underestimation of subclinical markers of other systems partaking. It leads to an incorrect interpretation of the true disease etiology, failure in genetic diagnostics, and untimely determination of the correct management and prognosis. The article presents clinical cases that demonstrate both the most typical manifestations of laminopathy and rare combinations of symptoms, which represent a certain diagnostic difficulty.